Infective endocarditis in octogenarians. Issue 20 (21st April 2017) - Oliver, Léopold; Lavoute, Cécile; Giorgi, Roch; Salaun, Erwan; Hubert, Sandrine; Casalta, Jean-Paul; Gouriet, Frédérique; Renard, Sebastien; Saby, Ludivine; Avierinos, Jean-Francois; Maysou, Laurie-Anne; Riberi, Alberto; et al.
Abstract : Objective: To describe the characteristics of infective endocarditis (IE) in octogenarians and assess their prognosis. Methods: Patients with definite IE hospitalised at a referral centre between July 2008 and July 2013 were prospectively included. A total of 454 patients were divided into three groups: 230 patients under 65 years old, 173 patients between 65 and 80 years old, and 51 patients over 80 years old. The main end point was 1-year mortality. Results: One-year mortality was higher in the ≥80 years old group (37.3%) than in the <65 years old group (13%; p<0.001) and the 65–80 years old group (19.7%; p=0.009). Enterococci and Streptococcus gallolyticus were the more frequent micro-organisms. Embolism under antibiotic therapy (n=11 (21.6%), p=0.03) and renal failure (n=23 (51%), p=0.004) were more frequent in the ≥80 years old group. Among the ≥80 years old group, 38 patients had theoretical indication for surgery. Mortality was low (6.3%) in the 16 operated patients, but very high (72.7%) in the 22 patients not operated. Even if octogenarians were less often operated, their survival after surgery was excellent like younger patients (93.7%, 89.9% and 90.4%, respectively), whereas the absence of surgery was associated with very poor prognosis. Conclusions: IE in octogenarians is a different disease, with Enterococci as the most frequent micro-organisms and with higher mortality than younger patients. ESC recommendations for surgery are less implemented than in younger patients, yielding dramatic mortality in patients not operated despite a theoretical indication for surgery, while operated patients have an excellent prognosis. These results suggest that surgery is underused in octogenarians.